2012
DOI: 10.1111/j.1365-2486.2012.02772.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining projected changes in species richness and composition reveals climate change impacts on coastal Mediterranean fish assemblages

Abstract: Species Temporal Turnover (STT) is one of the most familiar metrics to assess changes in assemblage composition as a consequence of climate change. However, STT mixes two components in one metric, changes in assemblage composition caused by a process of species loss or gain (i.e. the nestedness component) and changes in assemblage composition caused by a process of species replacement (i.e. the species replacement component). Drawing on previous studies investigating spatial patterns of beta diversity, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 48 publications
7
87
0
4
Order By: Relevance
“…Studies in the Mediterranean Sea confirmed this pattern, both in terms of observations (Galil, 2008;Zenetos et al, 2012) and future projections (Ben Rais Lasram et al, 2010;Albouy et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
“…Studies in the Mediterranean Sea confirmed this pattern, both in terms of observations (Galil, 2008;Zenetos et al, 2012) and future projections (Ben Rais Lasram et al, 2010;Albouy et al, 2012).…”
Section: Introductionsupporting
confidence: 52%
“…Poleward shifts in distributional areas were predicted (Albouy et al, 2012) and already recorded (Parmesan, 2006;Cheung et al, 2013), all around the world. According to the shifting scheme just reported, every species can simultaneously act as native loser and non-indigenous winner, depending on the perspective (original or new ecosystem, respectively), and the phenomenon of native species substitution with thermophilic non-indigenous invaders (eulerian view) can be seen as a simple species shifts (lagrangian view point).…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the simultaneous analysis of the relative effects of ecologically important predictor sets is essential to preventing misinterpretations of the ecological mechanisms that explain spatial distribution of marine biodiversity. With these results, we contribute to the current knowledge on the spatial distribution of marine biodiversity in the Mediterranean Sea (i.e., Albouy et al, 2012;Coll et al, 2010Coll et al, , 2012Lasram et al, 2010), advancing progress towards the development of more complex spatial analyses (Pennino et al, 2013;Steenbeek et al, 2013).…”
Section: Discussionmentioning
confidence: 84%